The Effect of Using Real Life Simulation and Language Game on Students Speaking Skill for Grade Ix Students of Junior High School - Tarigan, Ervina Br; Sinambela, Erika; Manik, Sondang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study delves into the realm of language pedagogy, focusing on the enhancement of Grade IX students' speaking skills at SMP Negeri 2 Merek. The research undertakes an analysis between two innovative language teaching methods, Real Life Simulation and Language Game, aiming to discern their respective impacts on oral proficiency. By exploring how these methods influence students' speaking abilities, educators can gain valuable insights into creating dynamic and effective language learning environments. The subject of this research was 90 students from three classes of ninth-grade students at SMP Negeri Satu Atap 2 Merek. The study employs pre-tests and post-assessment tests to collect comprehensive data. The analysis of this research was completed using t-test and two-way ANOVA from empirical experiments. The result of the use of Real Life Stimulation indicate that the method's impact on speaking abilities has a significance value of 0.003 <0.05. This demonstrates that kids' speaking skills are significantly impacted by the Life Simulation. On the otherÂ  hand, The use of Language Game indicate that the significant value of the impact of cognitive ability level was found to be 0.000 <0.05. This demonstrates that students' authentic materials technique has a major impact on their speaking skills. In conclusion, Real Life Simulation and Language Game methods are able to improve student speaking skill. For English teachers, it is recommended to apply this model in teaching English speaking mastery in the classroom to improve students' speaking skill. The findings are anticipated to contribute significantly to the ongoing discourse on innovative language teaching methodologies and their potential to enrich students' speaking skills in secondary education settings.